Desert Need Not Remain Desert - Misra, D.K.; Prasad, Ram; bhan, Suraj (Journal of Soil and Water Conservation, 2022)
Civilizations have been destroyed dui to -wind erosion, the dreary, awesome, natural phenomenon—the blind furry of the forces of nature, strong winds combined with man’s short sighted and selfish actions, indiscriminate felling of trees, overgrazing of grasslands, impro-per land-use and soil fertility exhaustion which have turned the whole areas of good earth into parched, dry deserts. But man, to be sure, is never helpless. The inexorable process can be halted and nature may forgive the faults of man and his animals.